Métodos multivariados aplicados ao melhoramento genético do feijoeiro visando ao aumento da tolerância ao estresse osmótico e biofortificação de grãos - Zanotti, Rafael Fonsêca (2015)
The common bean (Phaseolus vulgaris L.) is a very important crop economically and nutritionally for the Brazilian population and needs a simple and effective methodology that help the breeding process. The techniques should minimize the adverse effects of